Novel nanostructured materials based on polymer/organic-clay composite networks for the removal of carbendazim from waters - Baigorria, Estefanía [UNESP]; Fraceto, Leonardo F. [UNESP] (Elsevier, 2022)
Significant attention has been given to the development of nanocomposite polymeric hybrid materials for the removal of pesticides from water in recent decades. This study focused on the removal of carbendazim from aqueous systems using nanostructured composite hydrogels. The adsorbent systems were developed from polymeric networks composed of chitosan-organic clay. The materials were characterized by scanning electron microscopy, optical microscopy, X-ray diffraction, specific surface area studies, thermal and thermogravimetric analysis, infrared spectroscopy, point of zero charge, and aqueous adsorption analysis. In addition, the adsorption capacity of hydrogels for carbendazim in water was evaluated by batch tests. The adsorption studies responded to the pseudo-first-order kinetic model and Langmuir-type isotherms, with a maximum adsorption capacity of 0.4618 mg/g for the nanocomposite hydrogels. The results showed that the presence of organoclay as an active component of the hydrogels is critical in the process of carbendazim removal from aqueous systems. This indicates the potential of these new nanocomposite materials for use in treatment of water contaminated with carbendazim and other fungicides.
Keywords: Carbendazim; Chitosan; Fungicides; Hydrogels; Nano-clays; Water pollutants